2018
DOI: 10.1038/s41396-018-0073-5
|View full text |Cite
|
Sign up to set email alerts
|

Iron and phosphorus deprivation induce sociality in the marine bloom-forming cyanobacterium Trichodesmium

Abstract: Trichodesmium spp. are diazotrophic cyanobacteria that exist as single filaments (trichomes) and as macroscopic colonies of varying shapes formed by aggregating trichomes. The causes and dynamics of colony formation and disassociation are not yet elucidated. we demonstrate that limited availability of dissolved phosphorus (P) or iron (Fe) stimulated trichome mobility and induced colony formation in Trichodesmium erythraeum IMS101 cultures. The specific nutrient limitation differentially affected the rate of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 79 publications
4
28
0
Order By: Relevance
“…Our culture study suggests that Trichodesmium IMS 101 may use this protective strategy of adopting a colonial morphotype to help counteract inhibitory UV levels. This is consistent with a recent study by Tzubari et al (), who found that Trichodesmium IMS101 grew as single filaments during exponential growth, but formed colonies under oxidative stress or when limited by Fe or P. Although both IMS 101 and GBR died after several days under the highest UV‐B radiation treatment (1 W m −2 ), GBR did not use this potentially protective colonial strategy.…”
Section: Discussionsupporting
confidence: 92%
“…Our culture study suggests that Trichodesmium IMS 101 may use this protective strategy of adopting a colonial morphotype to help counteract inhibitory UV levels. This is consistent with a recent study by Tzubari et al (), who found that Trichodesmium IMS101 grew as single filaments during exponential growth, but formed colonies under oxidative stress or when limited by Fe or P. Although both IMS 101 and GBR died after several days under the highest UV‐B radiation treatment (1 W m −2 ), GBR did not use this potentially protective colonial strategy.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast with a recent laboratory study by Tzubari et al . (), we therefore assumed that, in our experiment, colony formation was not induced by P‐ or Fe‐depletion. As we did not observe any differences in abiotic conditions or cellular composition between free‐floating trichomes and colonies, the triggers for colony formation could not be identified.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, Trichodesmium cells (and its epibionts) appeared to act in concert to preserve new N from N 2 fixation in close proximity, to fully benefit from bioavailable N in the oligotrophic near-surface ocean. Trichodesmium colonies may thus be described as consortia, reflecting associations of synergistic, mutualistic or syntrophic lifestyles [99,100], in which the growth and elemental cycling are more efficient than on a single-population level.…”
Section: Nomentioning
confidence: 99%